EXPRESSION OF SOLUBLE ADENYLYL CYCLASE (sAC) IN LENTIGO MALIGNA: USE OF IMMUNOHISTOCHEMISTRY WITH anti-sAC ANTIBODY (R21), IN DIAGNOSIS OF LENTIGO MALIGNA AND ASSESMENT OF MARGINS - Magro, Cynthia M. (2012)
BACKGROUND: Soluble adenylyl cyclase (sAC) is an enzyme that generates cyclic adenosine monophosphate (cAMP), a signaling molecule involved in regulating melanocyte differentiation, proliferation and melanogenesis. R21, a mouse monoclonal antibody against sAC, shows a pattern of pan nuclear staining in lentigo maligna showing possible utility for diagnosis and for margin assessment. DESIGN: 31 re-excision specimens for lentigo maligna were evaluated for R21 expression using a previously published protocol. In addition, a prospective analysis of 123 cases including 41 lentigo malignas, 30 non-lentigo maligna type melanomas, 38 lentigos and 44 benign nevi were evaluated using a modified stringent protocol that eliminates non-melanocyte staining. RESULTS: The sensitivity of nuclear staining with R21 in lentigo maligna was 87.8%. Nuclear expression of sAC was observed in 40% of other melanomas and in only 2.3% of the benign nevi. R21 did not stain nuclei of resting melanocytes but nuclear staining was observed in 28.9% of melanocytic hyperplasias. R21 staining facilitated extent of the lesion in resection margins. In cases examined under the less stringent conditions interpretation can be facilitated by comparing R21 and Mart1/Melan A staining. Greater than 9 pan nuclear staining melanocytes within one high power field along with a pan nuclear sAC/melan A ratio >0.5 was consistent with a positive margin while five or less pan nuclear staining melanocytes along with a sAC/melan A ratio of <0.3 constituted a negative margin. CONCLUSION: R21 is a useful diagnostic adjunct in the diagnosis of lentigo maligna and can facilitate the evaluation of margins in re-excisions.